Steric and Electronic Manipulation of the Anagostic Interaction in 1‐Tetralone Oxime and Imine Complexes of Rhodium(I). Issue 1 (7th December 2015) - Harrison, John A.; Nielson, Alastair J.; Sajjad, M. Arif; Saunders, Graham C.; Schwerdtfeger, Peter
Abstract: Structures and properties for the complexes [RhCl(CO)2 (L)] (L = 1‐tetralone oximes and imines) containing anagostic C–H separations were obtained from density functional calculations using the dispersion corrected PBE‐D3 functional. Bench‐top syntheses were carried out for several complexes to obtain NMR spectral comparisons. The calculations show a ligand (N)–OH group positions the anagostic hydrogen (H 8 ) more over the metal and (N)–OCMe3 and (N)–CMe3 groups more out towards the chloro ligand where weak H··· Cl bonding is involved. This positioning is a result of varying Rh–N bond lengths and steric factors arising below the coordination plane where methyl‐group H atoms can form additional anagostic approaches to the metal and weak hydrogen bonds with the chloro ligand. QTAIM analysis indicates weak electrostatic repulsion for the Rh··· H 8 approaches. Disparity between the metal and C–H bond orbital energies precludes covalency. Both σ and π‐withdrawing substituents para to C 8 increase the H 8 positive charge lengthening the Rh··· H 8 separation; σ and π‐donating substituents decrease the charge and shorten the separation. For (N)–OH ligands, the C 7 ‐alkyl groups Me, CHMe2 and CMe3 do not affect the lengths of the Rh··· H 8 separations by a steric effect and no significant electronic effects are observed for C 7 ‐NO2, OMe or F substituents. A combination of an (N)‐CMe3 group and electron‐donating groups at C 5 and C 7 of the aromatic ring do not effect the Rh··· H 8 separation but the Rh··· C 8 separation decreases significantly leading to a C‐anagostic interaction. For all the complexes the ligand adapts to accommodate the anagostic approaches. Abstract : Computations show that the in the Rh I complexes, [RhCl(CO)2 (L)], where the ligands L are 1‐tetralone imines, the approach the anagostic hydrogen makes to the metal can be manipulated by steric changes made at the (N)–R section of the ligand and by electronic changes made on the aromatic ring.